Análisis de las variables sociodemográficas para identificar los cuidadores que están a cargo de la salud oral de los niños en el departamento de Santander, según el ensab iv año 2014. (2020)
Analyze the sociodemographic variables that identify the caregivers who are in charge of the oral health of children in the Department of Santander, according to the ENSAB IV year 2014, in order to train caregivers and update the information base with a topic of relevance in promotion and prevention to provide populations with the necessary means to improve health and exercise greater control over it, through the intervention of the determinants of health, the reduction of inequity and inclusion.